Neighbourhoods of Poverty
XI, 259 p. 17 illus.
Keywords: Neighbourhoods of Poverty is concerned with the spatial dimension of urban social exclusion and integration. It draws on research from twenty-two neighbourhoods in eleven European cities: Amsterdam, Rotterdam, Brussels, Antwerp, London, Birmingham, Berlin, Hamburg, Milan, Naples and Paris and addresses two questions: - How do different neighbourhoods have an impact upon the opportunities and perspectives of poor individuals and households? - Are these neighbourhood impacts conditioned by national and welfare state contexts, by the wider metropolitan structures and by specific neighbourhood characteristics? Various aspects of poverty, social exclusion and integration are brought together and provide a new assessment of the place of neighbourhood within these wider debates.